MODIS NDVI Modified Z-score for Evaluating Drought Incidence of Rice Areas in the Mekong Delta - Aunario, Jorrel Khalil; Laborte, Alice G. (International Rice Research Institute, 2023)
Extreme climate events such as flood, drought, and high temperature are expected to increase in frequency and intensity with climate change. Mapping and characterization of food production areas at risk can help in better targeting innovations and in enhancing the resilience of affected communities. In this study, we used two decades of the Moderate Resolution Imaging Spectroradiometer (MODIS) Normalized Difference Vegetation Index (NDVI)[1][2] from 2003 to 2022 to map drought incidence in rice areas in the Mekong Delta, a densely populated region and an important source of rice for domestic and export markets.